Training on Pivot Tables and Dashboard Creation for Medical Record Professionals at 'Aisyiyah General Hospital Padang - Yuli Mardi; Annisa Wahyuni; Muhammad Fajar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Pivot tables are one of the features found in Microsoft Excel. With pivot tables, data can be presented based on the selected categories. Data in a pivot table is presented in columns or rows. To make the data easily understandable for anyone reading it, the data can be displayed in the form of a dashboard. There is a lot of patient data stored in the database of 'Aisyiyah General Hospital Padang. This data can be utilized by medical record personnel as reports for management decision-making in the hospital. To ensure easy understanding, the data is presented in an attractive dashboard format. However, the professional medical record staff in the hospital and other medical personnel do not yet have the ability to create dashboards using pivot tables. Therefore, training is needed to implement this. The training will be held at 'Aisyiyah General Hospital Padang for two days, consisting of theoretical material as well as practical exercises based on data obtained from the hospital's database. The training conducted should proceed smoothly, and participants should be able to understand pivot tables, dashboards, and how to create them. Initially targeted at medical record personnel, the training program was also attended by other medical staff, including doctors, training department heads, and the hospital director. The training that has been conducted has expanded the participants' understanding of pivot tables, dashboards, and the significant benefits of Microsoft Excel's features. In the future, it is hoped that this training can be extended with a longer duration and cover other cases within the hospital.